Tribological study of nanoparticles enrichedbio-based lubricants for engine piston ring–cylinder interaction / Mubashir Gulzar - Mubashir, Gulzar (2017)
Given continuous environmental legislation, the lubrication industry has been striving to produce environmentally suitable lubrication alternatives for internal combustion engines. Addressing this challenge requires the use of lubricants that conform to environmental standards while maintaining excellent lubrication performance. This thesis investigates the tribological viability of bio-based base stock to which different nanoparticles were incorporated for engine piston ring–cylinder liner interaction. The specific base stock examined was trimethylolpropane (TMP) ester derived from palm oil, and the nanoparticles were used as additives to obtain tribologically enhanced bio-based lubricants. Nano sized additives included copper oxide, molybdenum disulfide and titanium silicate nanoparticles as lubricant additives. The effects of lubricating oil conditions (new and engine-aged) on the friction and wear of the materials used for piston rings and cylinder liners were experimentally determined. The research began with investigation of wear protection and friction reduction behavior of palm oil-derived TMP ester for piston ring–cylinder liner interaction. It was followed by the investigation of lubrication behavior of variety of nanoparticles as additives to palm TMP ester. The friction and wear characteristics of the lubricant samples were examined in contact conditions that were simulated using a high-stroke reciprocating tribometer. Four-ball tribo-testing was conducted to evaluate the extreme pressure characteristics of the samples. Suitable nanoparticle types and concentrations were then evaluated to enhance wear protection and reduce friction. Finally, surface analyses were carried out to ascertain potential lubrication mechanisms contributed by nanolubricants. In the next stage of the research, bio-based nanolubricant degradation under actual engine conditions and its tribological effect on the piston ring–cylinder liner combination was examined. Long duration engine testing was carried out using a single-cylinder compression ignition engine. To control lubricant acidity, a chemically active filter technology was used during engine bio-based lubrication. Engine sump oil samples were collected and analyzed for their physicochemical and tribological properties in comparison to a conventional diesel engine lubricant. The results have shown that friction reduction and antiwear behavior of palm TMP ester can be improved by addition of suitable concentrations of considered nanoparticles. The most significant improvement in the lubrication performance of palm TMP ester has been shown by 0.75 wt% of titanium silicate nanoparticles. A reduction of 68% in average friction coefficient was observed while wear volume was reduced to half for piston ring and cylinder liner specimen. The surface analysis results showed that the nanoparticles improved the lubrication performance by surface enhancement of interacting surfaces in terms of tribofilm formation, polishing and mending effects. Bio-based nanolubricant showed high degradation during long hours’ engine tests resulting in 17% lower viscosity, 30% high acidity and 16.8% higher oxidation than that of conventional engine oil. However, the friction and wear behavior of corresponding engine-aged samples were comparable to that of engine-aged conventional engine lubricant samples. The overall analysis of results demonstrated the potential of nanoparticles to improve the tribological behavior of bio-based base stock for piston ring–cylinder liner interaction.